RESEARCH OF CONDITIONS OF BARRIER-FREE ACCESS FOR PEOPLE WITH DISABILITIES TO THE BUILDING OF THE MYKHAILO BOICHUK KYIV STATE ACADEMY OF DECORATIVE APPLIED ARTS AND DESIGN - Rastvorov, Illia (Theory and practice of design, 2025)
Purpose. The research is aimed at finding and analyzing technical solutions for developing a ramp project for the main entrance of the Mykhailo Boichuk Kyiv State Academy of Decorative Applied Arts and Design. The goal is to ensure unimpeded access to educational services for people with disabilities. Methodology. The study employs methods of analyzing normative documents on building inclusivity, statistical data on the number of people with disabilities in Ukraine, and studying universal design principles. A comparative analysis of three ramp planning solutions was conducted based on criteria of functionality, usability, structural optimization, and compliance with regulatory norms. Results. The current accessibility situation of the main entrance to the Mykhailo Boichuk Kyiv State Academy of Decorative Applied Arts and Design building was analyzed, revealing non-compliance with inclusivity standards. Three ramp design options were developed, ensuring access to the entrance group and meeting the requirements of DBN V.2.2-40:2018 «Inclusivity of Buildings and Structures». An optimal ramp variant was proposed from the perspectives of functionality, ease of use for low-mobility groups, and cost-effectiveness of the structural solution. Scientific novelty. Consists of a comprehensive application of universal design principles to a specific architectural object, taking into account the specifics of using the building as an art-oriented higher education institution. Practical relevance. The research results can be utilized in modernizing entrance groups of other educational institutions to provide inclusive access to education for people with disabilities.